Early loading of implants with fixed dental prostheses in edentulous mandibles: 4.5-year clinical results from a prospective study - Kappel, Stefanie; Gabbert, Olaf; Hassel, Alexander J.; Schmitter, Marc; Séché, Anne-Christiane; Rammelsberg, Peter (Clinical oral implants research, 2010)
The purpose of this study was to evaluate the survival and success of early-loaded implants placed in the intraforaminal area of the edentulous mandible, and the survival of the implant-supported fixed dental prostheses (FDP). 5520 |s|early loading
Gesehen am 11.07.2023